Medical ethics in a multicultural country: differences in principles ad practices among Muslims and Buddhists - Goh, Kian Liang; Sharifudin, Mohd Ariff; Che Ahmad, Aminudin; Mohd Yusof, Nazri; Ab. Rahman, Norhafiza (IIUM Press, 2015)
Religion plays an imperial role in the ever-changing healthcare system of Malaysia. The Malaysian, being a multi-racial society, has to adapt and accommodate various practices of religion from different cultural and religious backgrounds. It is this diversity that demands the understanding of the different ideologies of faith as a necessity to the healthcare giver such as doctors, nurses, and paramedics. This article aims to compare the principles and practices of the official religion of Malaysia, Islam, as compared to the mainstream religion of the Chinese, which is Buddhism. The discussions focus on the general beliefs and practices of these two religions, the approach towards health and disease and dealing with the issues of death and dying.